Pemanfaatan Mesin Penggiling Ikan dan Mesin Pendingin Dalam Usaha Home Industry di Oesapa Kupang Nusa Tenggara Timur - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya (Yayasan Lavandaia Dharma Bali, 2021)
Management and processing of marine and fishery products are one of the ways to improve the welfare and socio-economy of the community. The province of East Nusa Tenggara is one of the regions in Indonesia that has enormous marine fishery potential. The potential for fisheries comes from capture fisheries and aquaculture reaching 72 thousand tons with a production value of 1.8 trillion Rupiah, and the second-largest seaweed producer after South Sulawesi with seaweed production of 2.9 trillion Rupiah. This potential needs to be developed to support economic growth and improve the welfare of people who have jobs in the fisheries sector, such as the development of value-added fishery products through fishery industrial activities. This activity aims to examine the added value of marine and fishery products on a home scale industry and its implications for society. This community service activity is carried out on Oesapa Beach by targeting coastal communities. Activities are carried out by providing training and presentation of material regarding the use of fish grinding machines and cold storage to properly and safely support small-scale economic activities. This activity was well appreciated by the community and had a positive impact in efforts to increase the selling power of marine and fishery products.